A possible origin of viscosity in Keplerian accretion disks due to secondary perturbation: Turbulent transport without magnetic fields - Mukhopadhyay, Banibrata; Saha, Kanak (Research in astronomy and astrophysics, 2011)
P1; The origin of hydrodynamic turbulence in rotating shear flow is a long standing puzzle. Resolving it is especially important in astrophysics when the flow's angular momentum profile is Keplerian which forms an accretion disk having negligible molecular viscosity. Hence, any viscosity in such systems must be due to turbulence, arguably governed by magnetorotational instability, especially when temperature T ≥ 105. However, such disks around quiescent cataclysmic variables, protoplan-etary and star-forming disks, and the outer regions of disks in active galactic nuclei are practically neutral in charge because of their low temperature, and thus are not expected to be coupled with magnetic fields enough to generate any transport due to the magnetorotational instability. This flow is similar to plane Couette flow including the Coriolis force, at least locally. What drives their turbulence and then transport, when such flows do not exhibit any unstable mode under linear hydrodynamic perturbation? We demonstrate that the three-dimensional secondary disturbance to the primarily perturbed flow that triggers elliptical instability may generate significant turbulent viscosity in the range 0.0001 ≤ vt≤ 0.1, which can explain transport in accretion flows.